Guardians of Childhood, Sentinels of Soul - Dykstra, Robert C. (Pastoral psychology, 2022)
This article builds on an address delivered in New York City in March of 2020 to the National Conference of the College of Pastoral Supervision and Psychotherapy, a professional society of clinical pastoral educators. Interweaving narrative reflections of noted authors, poets, filmmakers, and other artists with pastoral theological literature and recent genetic and social scientific research, the essay explores parameters of the soul or psyche as comprising the unique center of the self. It invites readers to a recovery of soul by means of arduous acts of introspection—revisiting lost childhood wonder, hope, memories, and dreams—and an embrace of pluralism and individual difference.